Uncorrected Tetralogy of Fallot with severe pulmonary stenosis in an adult: a case report - Sharma, Shraddha; Shetty, Sachin K.; A., Baskar; Priyadarshee, Piyoosh (International Journal of Research in Medical Sciences, 2025)
Tetralogy of Fallot (TOF) is a complicated cyanotic congenital heart problem that is uncommon in adults where it is uncorrected. The present case report tells about a patient of 35 years, who had uncorrected TOF and severe pulmonary stenosis, who came with complaints of cough and chest pain. Post-contrast CT depicted that main pulmonary artery, right pulmonary artery, and left pulmonary artery were severely constricted (5.3 mm, 5.8 mm, 5.5 mm), ascending aorta showed aneurysmal dilation (4.9 cm) and aorta arch (3.9 cm), and presence of various aortopulmonary collaterals. Other positive results were right ventricular hypertrophy, bilateral perinephric collections, fibrosis, and ground-glass lung opacities, partially attributable to previous tuberculosis. The results indicate the balancing vascular responses that maintain survival, the systemic sequelae of chronic hypoxemia and immediate dangers such as aortic rupture. The case indicates the necessary approach to multidisciplinary management and adds unique knowledge to unresolved TOF adult outcomes.